PENERAPAN RESTORATIVE JUSTICE DALAM TINDAK PIDANA DI BIDANG KETENAGAKERJAAN - Zenno Januarsyah, Mas Putra (LITIGASI, 2024)
In practice, a significant number of criminal cases within the domain of employment have been resolved through the implementation of restorative justice methodologies, particularly in instances where wage violations have occurred below the established minimum wage. However, there are no specific regulations governing the implementation of restorative justice as a mechanism for resolving criminal cases in the employment sector. The issues addressed in this research pertain to the regulation of restorative justice in the resolution of criminal cases in the field of employment in Indonesia and the implementation of restorative justice in the resolution of labor crime cases. This research is descriptive and of a normative juridical nature, utilizing secondary data in the form of primary legal materials, secondary legal materials, and tertiary legal materials. It employs a statute approach and a case approach, and is subsequently analyzed using qualitative methods. The research findings indicate that there is no specific legislation governing the implementation of restorative justice in the resolution of criminal cases pertaining to labor in Indonesia. However, the Prosecutor's Regulation Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice and Republic of Indonesia State Police Regulation Number 8 of 2021 concerning Handling of Criminal Acts Based on Restorative Justice may serve as a potential reference point for the application of restorative justice in labor-related offenses. Then, the application of restorative justice in resolving criminal cases has in practice been carried out in cases of criminal violations of employment in paying wages...